The authors of economics journals revisited: Evidence from a large-scale replication of Hodgson & Rothman (1999) - Matthias Aistleitner; Jakob Kapeller; Dominik Kronberger (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2022)
In this paper, we present results from of a large-scale replication of Hodgson and Rothman's (1999) seminal analysis of the institutional and geographical concentration of authors publishing in top economic journals. We analyze bibliometric data of more than 49.000 articles published in a set of 30 highly influential economic journals between 1990 and 2018. Based on a random sample of 3.253 authors, we further analyze the PhD-granting institutions of the authors under study to better scrutinize the claim of an institutional oligopoly. The findings confirm the long-term persistence of strong oligopolistic structures in terms of both, author affiliations as well as PhD-granting institutions.
Keywords: A14; B20; 330; sociology of economics; bibliometrics; concentration in science; replication study